(untitled) (Research, Society and Development, 2020)
Objective: Examine the evolution of publications on the lifestyle risk behaviors of university students. Methods: Bibliometric research was carried out on using 9011 articles retrieved from the SciELO and Web of Science database. The analyses included, the trend of the production, the most productive countries, journals, institutions, and the relevant information was extracted based on frequency of co-occurrence of keywords between 2009 and 2019 using the bibliometric software, namely VantagePoint, VOSviewer, NetDraw and UCINET. Results: The study revealed a significant concentration of publications between 2014 and 2018 in North American countries, especially the United States. However, the most productive institution was the University of São Paulo (Brazil). Stress, physical inactivity, obesity, and smoking were the risk behaviors most used as keywords in the articles, and these have a strong relationship with other keywords subsets related to mental health, forms of treatment, the study population and lifestyle behaviors. Conclusion: The scientific map of lifestyle risk behaviors among university students was supported by exhaustive research. It was possible by the establishment of research networks between the various centers of knowledge production, especially with the American researchers.